Homeopathic Formulations of Syzygium jambolanum Alleviate Glycation-Mediated Structural and Functional Modifications of Albumin: Evaluation through Multi-Spectroscopic and Microscopic Approaches - Bangar, Nilima S.; Ravindran, Selvan; Shaikh, Shamim A.; Shah, Nilesh; Tupe, Rashmi S. (Homeopathy, 2023)
Background The growing interest in identifying the mode of action of traditional medicines has strengthened its research. Syzygium jambolanum (Syzyg) is commonly prescribed in homeopathy and is a rich source of phytochemicals.Objective The present study aims to shed light on the anti-glycation molecular mechanism of Syzyg mother tincture (MT), 30c, and 200c on glycated human serum albumin (HSA) by multi-spectroscopic and microscopic approaches.Methods The phytochemicals and antioxidant potential of the Syzyg formulations were estimated by the high-performance liquid chromatography and spectroscopic technique, respectively. Glycation was initiated by incubating HSA with methylglyoxal, three Syzyg formulations, and the known inhibitor aminoguanidine in separate tubes at 37°C for 48 hours. The formation of glycation adducts was assessed by spectrofluorometer and affinity chromatography. The structural modifications were analyzed through circular dichroism, Fourier transform infrared spectroscopy, turbidity, 8-anilinonapthalene-1-sulfonic acid fluorescence, and nuclear magnetic resonance. Further, the formation of the aggregates was examined by thioflavin T, native-polyacrylamide gel electrophoresis, and transmission electron microscopy. Additionally, the functional modifications of glycated HSA were determined by esterase-like activity and antioxidant capacity. The binding analysis of Syzyg formulations with glycated HSA was evaluated by surface plasmon resonance (SPR).Results Syzyg formulations MT, 30c, and 200c contained gallic acid and ellagic acid as major phytochemicals, with concentrations of 16.02, 0.86, and 0.52 µg/mL, and 227.35, 1.35, and 0.84 µg/mL, respectively. Additionally, all three formulations had remarkable radical scavenging ability and could significantly inhibit glycation compared with aminoguanidine. Further, Syzyg formulations inhibited albumin's structural and functional modifications. SPR data showed that Syzyg formulations bind to glycated HSA with an equilibrium dissociation constant of 1.10 nM.Conclusion Syzyg formulations inhibited the glycation process while maintaining the structural and functional integrity of HSA.
Keywords: albumin; glycation; homeopathy; Syzygium jambolanum